2021
DOI: 10.1186/s12879-021-06001-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of parainfluenza infections among young children hospitalized for acute respiratory illness in Amman, Jordan

Abstract: Background Parainfluenza virus (PIV) is a leading cause of acute respiratory illness (ARI) in children. However, few studies have characterized the clinical features and outcomes associated with PIV infections among young children in the Middle East. Methods We conducted hospital-based surveillance for ARI among children < 2 years of age in a large referral hospital in Amman, Jordan. We systematically collected clinical data and respiratory spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…HPIV-4 has been considered rare in the past, in part due to underdiagnosis because it was more difficult to isolate and type-specific molecular methods were lacking [ 22 , 54 , 64 ]. Others have found HPIV-4 to represent between 8% and 22% of HPIV-positive samples and given that the frequency of detection for each type is subject to annual fluctuations, the frequencies determined for our study population match these findings well [ 23 , 53 , 55 , 63 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…HPIV-4 has been considered rare in the past, in part due to underdiagnosis because it was more difficult to isolate and type-specific molecular methods were lacking [ 22 , 54 , 64 ]. Others have found HPIV-4 to represent between 8% and 22% of HPIV-positive samples and given that the frequency of detection for each type is subject to annual fluctuations, the frequencies determined for our study population match these findings well [ 23 , 53 , 55 , 63 ].…”
Section: Discussionsupporting
confidence: 81%
“…Our findings are consistent with those of Frost et al [ 20 ], who described year-round PIV-4 prevalence with peaks in the fall of odd-numbered years. Peaks in the fall have been described for this HPIV type previously [ 2 , 13 , 23 , 63 , 64 ], and one group of investigators also commented on the biennial circulation pattern of HPIV-4 [ 64 ]. Given that HPIV-4 has not been detected in many studies, our investigations help to address the paucity of seasonality data on this HPIV type.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, PIV-3 showed a higher prevalence, as it was detected in 33% of cases, most of them under five years old. This is consistent with data that; PIV is identified as a substantial causative agent of pneumonia in children (Howard et al 2021 ). However, a recent Egyptian study reported a lower prevalence rate of PIV-3 (7%).…”
Section: Discussionsupporting
confidence: 93%